Synthesis and characterization of allomelanin model from 1,8-dihydroxynaphthalene autooxidation - Jan Pukalski; Krystian Mokrzyński; Marek Chyc; Marek J. Potrzebowski; Tomasz Makowski; Mateusz Dulski; Dariusz Latowski (Scientific Reports)
Abstract In this work a novel method for synthesis of 1,8-dihydroxynaphthalene melanin was presented, as well as the physicochemical properties, molecular structure, and characteristics of the pigment. The proposed synthesis protocol is simple and cost-effective with no enzymes or catalysts needed. The final product is not adsorbed on any surface, since the pigment is the result of autooxidation of 1,8-dihydroxynaphthalene. Performed analyses revealed that the solubility, optical and paramagnetic properties are typical for melanins, and in the EPR spectra an unusual hyperfine structure was observed. The molecular structure of the pigment consists of three different layers forming polar and non-polar surfaces. Additionally, the presence of ether bonds presence was revealed. The developed method creates new opportunities for melanin research and eliminates the need to extract melanins from biological samples, which often lead to structural changes in isolated melanins, which undermines the reliability of analyses of the properties and structure of these polymers. On the other hand, the ubiquity of melanins in living organisms and the diversity of their biological functions have let to the growing interest of researchers in this group of pigments. The analyses carried out show that the obtained synthetic DHN polymer can be considered as a model DHN-melanin in mycological studies and material research.